Green endoscopy: British Society of Gastroenterology (BSG), Joint Accreditation Group (JAG) and Centre for Sustainable Health (CSH) joint consensus on practical measures for environmental sustainability in endoscopy. Issue 1 (13th October 2022) - Sebastian, Shaji; Dhar, Anjan; Baddeley, Robin; Donnelly, Leigh; Haddock, Rosemary; Arasaradnam, Ramesh; Coulter, Archibald; Disney, Benjamin Robert; Griffiths, Helen; Healey, Christopher; Hillson, Rosie; Steinbach, Ingeborg; et al.
Abstract : GI endoscopy is highly resource-intensive with a significant contribution to greenhouse gas (GHG) emissions and waste generation. Sustainable endoscopy in the context of climate change is now the focus of mainstream discussions between endoscopy providers, units and professional societies. In addition to broader global challenges, there are some specific measures relevant to endoscopy units and their practices, which could significantly reduce environmental impact. Awareness of these issues and guidance on practical interventions to mitigate the carbon footprint of GI endoscopy are lacking. In this consensus, we discuss practical measures to reduce the impact of endoscopy on the environment applicable to endoscopy units and practitioners. Adoption of these measures will facilitate and promote new practices and the evolution of a more sustainable specialty.